Structure and dynamics an atomic view of materials - Dove, Martin T. (Oxford Oxford University Press, 2003)
This book is concerned with a wide range of general principles that govern the behaviour of atoms in solids, and these principles are applied to the full range of types of materials known to man. The dual focus is on the structures of materials at an atomic level and on how the atoms vibrate inside solids. This dual focus comes together to explore how the atomic principles determine the behaviour and properties of materials. Attention is also given to experimental methods. The general principles include the factors that determine the packing of atoms to form the huge variety of structures, the formal description of real and reciprocal space, the types of atomic bonding, the formalism of atomic vibrations, and the theories of phase transitions. The tools covered include diffraction and spectroscopy, both laboratory and large-scale facilities. Contents :- Preface 1. Introduction 2. Structure of materials 3. Formal description of crystal structures 4. The reciprocal lattice 5. Atomic bonding in crystals 6. Diffraction 7. Physical properties 8. Lattice dynamics 10. Experimental methods for measurements of vibrational frequencies 11. Anharmonic interactions 12. Displacive phase transitions A. Real crystals! B. Fourier analysis C. Schoenflies representation of the point groups D. Rhombohedral, trigonal and hexagonal unit cells E. Space groups F. Lattice energy minimization G. Some note on the variational theorem H. Ewald Sphere I. The Wilson Plot J. Diffraction from isotropic materials K. Calculation of physical properties L. Partition function: some key results M. Lattice sums N. Mean-square atomic displacement and temperature factors References Index. About the Author :- Martin T. Dove is Reader in Computational Mineral Physics, Department of Earth Sciences, Cambridge University.
Keywords: Solid state physics; Matter -- Constitution; Matter -- Properties